PENERAPAN SIKLUS MENU BERBASIS OLAHAN LAUT BAGI BALITA DI WILAYAH KERJA PUSKESMAS PADANG SERAI - emi yuliantini; Kamsiah kamsiah; Ayu Pravita (Jurnal Pengabdian Kepada Masyarakat Pusat Unggulan Iptek Penanggulangan Stunting Berbasis Kesehatan Ibu dan Anak, 2026)
Stunting remains a chronic nutritional problem in Indonesia with a prevalence of 21.6% according to the 2022 Indonesian Nutritional Status Survey (SSGI), still far from the national target of 14% in 2024. In Bengkulu City, particularly in the Padang Serai Community Health Center (Puskesmas Padang Serai), stunting rates are quite high, especially among fishing families who have limited access to nutritious food. This community service activity aims to increase the understanding of mothers of toddlers regarding the importance of seafood consumption in preventing stunting, improve skills in preparing balanced nutritious menus based on seafood, and support the national convergence program to reduce stunting. Implementation methods include stunting identification and mapping, nutrition socialization and education, training in preparing seafood menu cycles, menu implementation in households, and monitoring and evaluation through pre-post tests and toddler anthropometric measurements. The results of the activity showed success in increasing the knowledge and skills of mothers of toddlers regarding the implementation of seafood-based menu cycles. Based on the results of the pre-test and post-test, there was an average increase in knowledge of 32.5%, covering aspects of balanced nutrition, the benefits of consuming sea fish, menu preparation skills, and stunting prevention. This shows that the participatory educational approach and direct practice are effective in increasing participants' understanding.